Defects in the Expression of Chloroplast Proteins Leads to H2O2 Accumulation and Activation of Cyclic Electron Flow around Photosystem I - Strand, Deserah D.; Livingston, Aaron K.; Satoh-Cruz, Mio; Koepke, Tyson; Enlow, Heather M.; Fisher, Nicholas; Froehlich, John E.; Cruz, Jeffrey A.; Minhas, Deepika; Hixson, Kim K.; Kohzuma, Kaori; Lipton, Mary; et al. (Frontiers in Plant Science, 2017)
We describe a new member of the class of mutants in Arabidopsis exhibiting high rates of cyclic electron flow around photosystem I (CEF), a light-driven process that produces ATP but not NADPH. High cyclic electron flow 2 (hcef2) shows strongly increased CEF activity through the NADPH dehydrogenase complex (NDH), accompanied by increases in thylakoid proton motive force (pmf), activation of the photoprotective qE response, and the accumulation of H2O2. Surprisingly, hcef2 was mapped to a nonsense mutation in the TADA1 (tRNA adenosine deaminase arginine) locus, coding for a plastid targeted tRNA editing enzyme required for efficient codon recognition. Comparison of protein content from representative thylakoid complexes, the cytochrome bf complex and the ATP synthase, suggests that inefficient translation of hcef2 leads to compromised complex assembly or stability leading to alterations in stoichiometries of major thylakoid complexes as well as their constituent subunits. Altered subunit stoichiometries for photosystem I, ratios and properties of cytochrome bf hemes, and the decay kinetics of the flash-induced thylakoid electric field suggest that these defect lead to accumulation of H2O2 in hcef2, which we have previously shown leads to activation of NDH-related CEF. We observed similar increases in CEF, as well as increases in H2O2 accumulation, in other translation defective mutants. This suggests that loss of coordination in plastid protein levels lead to imbalances in photosynthetic energy balance that leads to an increase in CEF. These results taken together with a large body of previous observations, support a general model in which processes that lead to imbalances in chloroplast energetics result in the production of H2O2, which in turn activates CEF. This activation could be from either H2O2 acting as a redox signal, or by a secondary effect from H2O2 inducing a deficit in ATP.